Factors associated with PEP awareness among adolescent girls and young women in Eswatini - Anne Laterra; Stephanie Spaid Miedema; Michelle Li; Phumzile Mndzebele; Nozipho Nzuza‐Motsa; Sana Nasir Charania; Katherine Ong; Meagan Cain; Udhayashankar Kanagasabai; Thobile Mkhonta; Laura Chiang; Francis Boateng Annor; et al. (Journal of the International AIDS Society, 2025)
Abstract Introduction In Eswatini, HIV incidence among adolescent girls and young women (AGYW), aged 15–24 years, is 10 times that of their male peers. Despite the World Health Organization's 2014 recommendation for post‐exposure prophylaxis (PEP) to be available for all HIV exposures, it has been underutilized among youth. PEP is an effective prevention method, and a better understanding of the characteristics, risk factors and behaviours that are associated with PEP awareness, as a precursor to effective use, is needed. Methods Using data from the 2022 Eswatini Violence Against Children and Youth Survey, we used logistic regression models to explore the relationships between PEP awareness and a set of hypothesized explanatory variables among AGYW aged 13–24 years who had ever had sex (N = 2648). Explanatory variables included socio‐demographic characteristics, sexual risk factors and sexual health behaviours. Results A slight majority (57.3%) of AGYW who had ever had sex were aware of PEP as an HIV prevention method. PEP awareness increased with age (aOR 1.1, 95% CI 1.0, 1.1) and was higher among AGYW who had a sexual partner whose age was 5 or more years older in the past 12 months (aOR 1.4, 95% CI 1.1, 1.9), those who had ever taken part in an HIV prevention programme (aOR 1.6, 95% CI 1.2, 2.3) and those who had ever heard of pre‐exposure prophylaxis (aOR 8.1, 95% CI 6.4, 10.2). Participants who were ever married or partnered (aOR 0.7, 95% CI 0.5, 1.0) and those who engaged in inconsistent condom use with non‐spouse/main partner or multiple partners in the past 12 months (aOR 0.8, 95% CI 0.6, 1.00) had lower odds of knowing about PEP in the adjusted model. Conclusions We identified sub‐optimal PEP awareness among Swazi AGYW who had ever had sex. Our findings suggest that engagement in HIV prevention programmes increased PEP awareness and that knowing about pre‐exposure prophylaxis (PrEP) was associated with PEP awareness. Future efforts could include tailored PEP awareness activities and campaigns to resonate with AGYW at elevated risk of HIV and integration of PEP education into routine sexual and reproductive service delivery and school‐based HIV curriculum.